Plasma TNFSF13B and TNFSF14 Function as Inflammatory Indicators of Severe Adenovirus Pneumonia in Pediatric Patients - Fan, Huifeng; Lu, Bingtai; Cao, Can; Li, Hui; Yang, Diyuan; Huang, Li; Ding, Tao; Wu, Minhao; Lu, Gen (Frontiers in Immunology, 2021)
Background: Adenoviruses (HAdV) infection caused pneumonia remains a major threat to global children health. Currently, diagnosis of severe HAdV pneumonia in children is hampered by the lack of specific biomarkers. Also, the severity of adenovirus pneumonia in pediatric patients is generally based on clinical features and existing biomarkers do not reliably correlate to clinical severity. Here, we asked whether local and systemic inflammatory mediators could act as biomarkers predicting severe HAdV pneumonia in children. Methods: 37 common inflammatory proteins protein levels were determined using Luminex assay in plasma and bronchoalveolar lavage (BAL) from pediatric patients who were diagnosed with HAdV pneumonia, and their correlation with the disease severity and lung lesion were assessed using statistical and bioinformatic analysis. Results: Among 37 inflammatory cytokines, the protein levels of 4 TNF superfamily (TNFSF) and their receptors (TNF receptor superfamily, TNFRSF) members [TNFSF13B, TNFSF14, sTNF-R1 and sTNF-R2] in the plasma and 7 TNFSF/TNFRSF members [TNFSF12, TNFSF13, TNFSF13B, TNFSF14, TNFRSF8, sTNF-R1 and sTNF-R2] in the BAL were enhanced in patients with HAdV pneumonia compared with control subjects with airway foreign body. Moreover, the protein levels of all the tested TNFSF/TNFRSF members (except TNFSF12) were elevated in the BAL of severe group compared with non-severe HAdV pneumonia patients, while only TNFSF13B and TNFSF14 were dramatically increased in the plasma of severe cases, and positively related to the plasma CRP levels. In addition, ROC analysis indicated that TNFSF13B and TNFSF14 displayed a great potential to predict severe HAdV pneumonia. Conclusion: In pediatric HAdV pneumonia, TNFSF/TNFRSF members function as key molecules in local and systemic inflammatory network, and the plasma TNFSF13B and TNFSF14 may be the potential local and systemic inflammatory indicators of severe HAdV pneumonia in pediatric patients. Key words: tumor necrosis factor superfamily, human adenovirus, pediatric, severe pneumonia, inflammation